Mujeres e historia. Los años de la experiencia (El Hilo de la Fabula, 2010)
The years of experience analyse the development of women’s studies in Spain, from their beginning, at the end of the 70’s, to today’s introduction at the University as gender studies. As a historian, the author is interested in the creation of a feminist historiography, pointing out the debates concerning the issue that have already taken place, as well as the foreign, French and American influences. Particularly, the fortune of the gender category has become a defining element in women’s studies at an international level. This category, however, is critically reviewed in view of the new reflections about the uses and abuses of this category. In this sense, the comprensión and communication problems that occur among experts as well as among the posible recipients of this theory and the feminist history are analysed, so a new debate is consequently opened.